Tingkat Distribusi Spasial dan Temporal Curah Hujan Terhadap Risiko Lingkungan dan Ketahanan Sumber Daya Air di Kota Tidore Kepulauan - Muhammad Ikhsan; Lili Somantri; Iwan Setiawan (Jurnal Pendidikan Geosfer, 2025)
This study aims to analyze the hydroclimatological dynamics in Tidore Islands City by integrating rainfall observation data with spatial-temporal visualization to identify rainfall distribution patterns, environmental risk zones, and provide locally grounded climate adaptation policy recommendations. Tidore is an archipelagic region that relies heavily on rainfall as the primary source of clean water and agricultural irrigation. The study employs a quantitative-descriptive approach combined with spatial analysis using Geographic Information Systems (GIS), utilizing rainfall data from five main observation stations collected over the 2019–2023 period. The analysis reveals significant spatial and temporal fluctuations in rainfall, with uneven distribution between humid and arid zones. The novelty of this research lies in the application of kriging-based spatial mapping to more accurately identify hydroclimatological risk areas—an approach that has not been widely developed in eastern Indonesia. This spatial visualization provides a critical foundation for regional spatial planning (RTRW), the designation of water conservation zones, and local climate disaster mitigation strategies. Abstrak Penelitian ini bertujuan untuk menganalisis dinamika hidroklimatologi di Kota Tidore Kepulauan melalui integrasi data observasi curah hujan dan visualisasi spasial-temporal guna mengidentifikasi pola distribusi hujan, zona risiko lingkungan, serta memberikan rekomendasi kebijakan adaptasi iklim berbasis lokal. Kota Tidore merupakan wilayah kepulauan yang sangat bergantung pada curah hujan sebagai sumber utama air bersih dan irigasi pertanian. Penelitian ini menggabungkan pendekatan kuantitatif-deskriptif dengan analisis spasial berbasis Sistem Informasi Geografis (SIG), menggunakan data curah hujan periode 2019–2023 dari lima pos pengamatan utama. Hasil analisis menunjukkan fluktuasi curah hujan yang signifikan secara spasial dan temporal, dengan ketimpangan distribusi antara wilayah lembab dan wilayah kering. Visualisasi spasial ini menjadi dasar penting dalam penyusunan RTRW, penentuan zona konservasi air, serta mitigasi bencana iklim lokal.